Load Balancing in DDOS- A proposed Methodology in WSNs - Bhawna, Mohit Marwaha, Baljinder Singh (International Journal of Advanced Science and Technology, 2020)
Wireless Sensor Networks (WSNs) usage has ameliorated rapidly over the period of time. Because of limited resources, wireless sensors face new problems regarding the security in a network and its energy consumption. Many researches focused on the availability of network, which proposes mechanisms to prevent network against DOS attacks by using method of traffic monitoring on specific nodes. These nodes further need to analyze the cluster traffic and send warnings to the cluster-head on observing an abnormal behavior. In this paper, first of all, a network of 50 nodes is constituted and then DDOS attack is detected. Also, a load balancing mechanism is implemented to overcome the problem of traffic congestion. Finally, DDOS attack is compared with DDOS and load balancing on the basis of Throughput, delay and Packet Delivery Ratio.